The Effect of Gross Domestic Product and Inflation on Value-Added Tax Revenue in Indonesia - Tengku Eka Susilawaty; Nancy Mayriski Siregar; Rifqy Cheviandri (Proceeding of The International Conference on Business and Economics, 2024)
This study aims to explore and empirically test the impact of Gross Domestic Product (GDP) and inflation on value-added tax (VAT) receipts. The research was conducted in Indonesia over the period from 1993 to 2022, using a sample of 30 observations on GDP, inflation and VAT. The sampling method employed was non-probability sampling with a saturation sampling technique, where the entire population was used as the sample. The analysis technique applied was multiple linear regression. The results indicate that, individually, GDP has a significant effect on VAT receipts (t-value > t-table) 2.064 > 2.059; an increase in GDP is likely to enhance VAT receipts due to the increase in household income, which supports the consumption of goods and services. In contrast, inflation does not have a significant effect on VAT receipts (t-value < t-table) 1.470 < 2.059; despite rising inflation, VAT receipts remain stable due to government policies on price controls, subsidies, and other measures to stabilize prices. Collectively, GDP and inflation together account for 98.2% of the effect on VAT receipts. Future research is recommended to include additional variables from both internal and external factors, such as government policies or global economic conditions, to gain a deeper understanding of other determinants affecting VAT receipts beyond GDP and inflation.